Sexism in “Digimon”: Fifteen years of stagnation - Vázquez-Miraz, Pedro (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
This paper describes an analysis of sexism that maintains a popular Japanese cartoon, “Digimon”. This program was first broadcast in Spain in 2000 and actually, continues to transmit the image of traditionalist gender roles to children who watch the program. We have compared the main personal characteristics that the program gives each one of the characters based on their sex and the goals they have achieved in the first two seasons of this longlived program, with the new audio-visual material that was introduced in 2015. Also we did a denotative analysis of four chapters of the first season, randomly selected, and the first four chapters of his final season. Conclusions are clear; in both materials, the male protagonists and their companions represent typical male stereotypes: strong leadership and importance of courage and strength; while women represent classic female roles: submissive attitude toward the group leader, great capacity for auto-sacrifice or show affection for each other.
Keywords: sexism; violence; social roles; gender stereotypes; cartoons; television